Without remorse ebook - Clancy, Tom (John Clark, 1994)
NOW A MAJOR MOTION PICTURE STARRING MICHAEL B. JORDAN—WATCH NOW ON PRIME VIDEO! From Tom Clancy, the celebrated author of the Jack Ryan series, comes the #1 New York Times bestseller that puts CIA operative John Clark front and center.... His code name is Mr. Clark. His work for the CIA is brilliant, cold-blooded and efficient...But who is he really? In a harrowing tour de force, Tom Clancy shows how an ordinary man named John Kelly crossed the lines of justice and morality to become the CIA legend, Mr. Clark. It is an unforgettable journey into the heart of darkness. Without mercy. Without guilt. Without remorse.